Financial Literacy as Mediates of Financial Attitude And Intention To Invest in Shariah - Utami, Eristy Minda; Yuliani, Reva; Fatihat, Gita Genia (ADPEBI International Journal of Business and Social Science, 2024)
Purpose – The primary goal of this investigation is to examine the intervening effect of financial literacy on the explanation of the link among financial attitude and the intent of Generation Z to make investments in Sharia-compliant financial products. Indonesia is progressively acknowledging the importance of investment in financial planning, which is being stimulated by the general public and breakthroughs in financial technology. However, Generation Z exhibits low investment intentions, necessitating efforts to enhance financial literacy and modify consumerist financial attitudes. Methodology/approach – This research employs an online survey targeting high school students at Al-Quran Qiroatusab'ah Islamic Boarding School (Madrasah Aliyah). Data on financial attitudes, financial literacy, and investment intentions were collected and analyzed using Structural Equation Modeling with Partial Least Squares (PLS). Findings – The study reveals that high school students financial attitudes significantly influence their financial literacy and investment intentions. The findings indicate that enhanced financial literacy positively impacts their intention to invest in Sharia-compliant financial products. Novelty/value – The research offers a comprehensive analysis of the interplay between financial literacy, financial attitudes, and investment intentions among students in Sharia banking at Islamic boarding schools in Indonesia, utilizing SEM-PLS methodology. This study provides insights into improving investment intentions through targeted financial literacy programs.